2017
DOI: 10.1101/gad.305631.117
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactive mTOR and MNK1 phosphorylation of eIF4E confer tamoxifen resistance and estrogen independence through selective mRNA translation reprogramming

Abstract: The majority of breast cancers expresses the estrogen receptor (ER) and is treated with anti-estrogen therapies, particularly tamoxifen in premenopausal women. However, tamoxifen resistance is responsible for a large proportion of breast cancer deaths. Using small molecule inhibitors, phospho-mimetic proteins, tamoxifen-sensitive and tamoxifen-resistant breast cancer cells, a tamoxifen-resistant patient-derived xenograft model, patient tumor tissues, and genome-wide transcription and translation studies, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 93 publications
2
43
1
Order By: Relevance
“…We speculate that translational offsetting plays a role in mediating biological effects of ERa in neoplastic tissues. Indeed, using a polysome-profiling data set comparing tamoxifensensitive vs. resistant cells (Geter et al, 2017a;Data ref: Geter et al, 2017b), we observed translational activation of mRNAs with higher requirements for U34-modified tRNAs and increased expression of ALKBH8 in tamoxifen-resistant cells (Appendix Fig S7). Thus, modulation of translation via ERa-dependent changes in U34-modifications may be associated with drug resistance and our findings therefore may have important implications in understanding alterations in gene expression programs following treatment with ERa antagonists.…”
Section: Of 19mentioning
confidence: 90%
“…We speculate that translational offsetting plays a role in mediating biological effects of ERa in neoplastic tissues. Indeed, using a polysome-profiling data set comparing tamoxifensensitive vs. resistant cells (Geter et al, 2017a;Data ref: Geter et al, 2017b), we observed translational activation of mRNAs with higher requirements for U34-modified tRNAs and increased expression of ALKBH8 in tamoxifen-resistant cells (Appendix Fig S7). Thus, modulation of translation via ERa-dependent changes in U34-modifications may be associated with drug resistance and our findings therefore may have important implications in understanding alterations in gene expression programs following treatment with ERa antagonists.…”
Section: Of 19mentioning
confidence: 90%
“…Furthermore, they predicted that increased levels or availability of eIF4E and increased eIF4E S209 phosphorylation by MNK1 would promote selective increased translation of RUNX2 mRNA. These findings suggest that high expression of RUNX2 would be expected to be involved in modulating tamoxifen response [28]. Indeed we found that treating the tamoxifenresistant cell line LCC2 with MNK inhibitor could reverse tamoxifen resistance ( Fig.…”
Section: Discussionmentioning
confidence: 53%
“…A recent report suggested that tamoxifen resistance involves genome-wide translational reprogramming to select for the translation of mRNAs mediated by increased expression and availability of eIF4E, through phosphorylation and its increased availability by hyperactive mTOR [28]. Through a knockdown approach, they uncovered that mitogen-activated protein kinase (MAPK)-interacting serine/threonine kinase (MNK), which mediates the phosphorylation of eIF4F at Ser209, is essential for modulating the downstream pathway of eIF4E, and further identified RUNX2 to be involved in modulating tamoxifen resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that this plays a role in mediating biological effects of ERα in neoplastic tissues. Indeed, using a polysomeprofiling data set comparing tamoxifen-sensitive vs. resistant cells (Geter et al, 2017), we observed translational activation of mRNAs with higher requirements for U34modified tRNAs and increased expression of ALKBH8 in tamoxifen-resistant cells (Supplementary Fig. S9).…”
Section: Discussionmentioning
confidence: 96%